Problem solving, Representations, Temporal relations, Number, Figure, Metacognition. - Σκοπελίτη Ειρήνη; Βοσνιάδου Στέλλα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
We present the results of two empirical studies which investigated the effect of the type of information included in refutational texts in 3rd grade students’ comprehension of the spherical shape of the earth. In the first study we compared three kinds of refutational texts: the first refuted only the belief that the earth is flat, the second refuted in addition the belief in up/down gravity, and the third refuted all of the above and in addition the belief that the earth is a physical and not an astronomical object. In Experiment 2, four texts were used to compare text type (refutation vs. non-refutation) and information type (categorical vs. non-categorical information). The results from the two experiments confirmed our hypothesis that refutational texts that include categorical information are the most effective in improving students’ understanding of scientific information about the earth.